Influences of Micelle Formation and Added Salts on the Hydrolysis Reaction Rate of p‐Nitrophenyl Benzoate in Aqueous Buffered Media. Issue 2 (13th December 2016) - Bayissa, Leta Danno; Ohmae, Yoshihito; Hojo, Masashi
ABSTRACT: The hydrolysis reaction rate of p ‐nitrophenyl benzoate ( p ‐NPB) has been examined in aqueous buffer media of pH 9.18, containing surfactants, cetyltrimethylammonium bromide (CTAB) and chloride (CTAC), or sodium dodecyl sulfate (SDS) at 35°C. Although the rate constant [log ( k /s −1 )] of p ‐NPB hydrolysis has once decreased slightly below the critical micelle concentration (CMC) value for CTAB and CTAC, it has begun to increase drastically with micellar formation. With increasing concentrations larger than the CMC value, the log ( k /s −1 ) value has reached the optimal value, i.e., a 140‐ and 200‐fold rate acceleration for CTAB and CTAC, respectively, compared to that without a surfactant. Whereas the anionic surfactant, SDS, has caused only a gradual rate deceleration in the whole concentration range (up to 0.03 mol dm −3 ). Increases in pH of the buffer have resulted in increases of the hydrolysis rate. In the CTAB micellar solution, the remarkably enhanced rate has been retarded significantly by the addition of only 0.10 mol dm −3 bromide salts. The effects of rate retardation caused by the added salts follows in the order of NaBr > Me4 NBr > Et4 NBr > Pr4 NBr > n ‐Bu4 NBr. In the absence of surfactant, however, the addition of the bromide salts has accelerated the hydrolysis rate, except for the metallic salt of NaBr, with the order of Me4 NBr < Et4 NBr < Pr4 NBr < n ‐Bu4 NBr. In the CTAC micellar solution, similar rate retardation effects have been observed in the presence of chloride salts (NaCl, Et4 NCl, and n ‐Bu4 NCl). The effects of added salts have been interpreted from the viewpoints of the changes in activity of the OH − ion and/or the nucleophilicities of the anions from the added salts.